Recruiting and Engaging Older Men in Evidence-Based Health Promotion Programs: Perspectives on Barriers and Strategies - Chelsie Anderson; Laura R. Seff; Anamika Batra; Chintan Bhatt; Richard C. Palmer (Journal of Aging Research)
Evidence-based health promotion programs are effective at reducing health risks and healthcare costs among older adults, but few men participate in the programs. This mixed methods study aimed to gain insight into the barriers to recruiting and engaging older men in evidence-based health promotion programs offered by the Healthy Aging Regional Collaborative of South Florida (HARC). Fourteen program coordinators participated in a focus group to identify barriers and strategies to improve male participation, and 49 instructors participated in a survey to triangulate the findings. Themes among barriers to male participation included women outnumbering men in the implementation sites and programs, conflict between male gender roles and the programs, and preference for other activities. Themes among strategies included public support of programs by male community leaders, program advertisements featuring males, and adapting program content. Survey results supported themes identified in the focus group. Nearly 78% of the survey respondents agreed that the perception of exercise programs as feminine was a barrier and over 90% of the survey respondents believed program advertisements featuring men would increase male participation. Findings indicate that health promotion programs and recruiting strategies need to be tailored to the unique needs and preferences of older men to improve participation.